ANALISIS PESAN DAKWAH VIDEO “JANGAN ADA DENDAM DAN KEBENCIAN KEPADA SIAPAPUN” PADA AKUN YOUTUBE KH. BUYA SYAKUR YASIN, M.A - Ali Sobirin; Muhammad Nur Kholis AR (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
YouTube is part of the internet. Everyone can use this media to do their da'wah, like Buya Syakur. The content that YouTube users are interested in is "Book Review", this content has topics of discussion from book studies such as the Book of Fathur Rabbani, the Book of Fi-Dhilalil Qur'an which explains human self-development. Therefore, researchers are interested in conducting research on Buya Syakur's content. This research is a qualitative descriptive research. Descriptive qualitative research is a formulation of the problem that guides research to explore or photograph social situations that will be examined thoroughly, broadly, and in depth, and the main instrument is the researcher himself. The results of the study show that there is a da'wah message, namely that we are not arrogant but always humble, not belittling other people, not looking down on others, not being arrogant, not believing that we are the most righteous, but must always be tolerant. We must not hold grudges and hate those who have wronged us, but must be easy to forgive. Not feeling the best in front of Allah even though we are diligent in worship so that we avoid the ujub nature. Allah is the one who has the prerogative of whoever is given guidance, no one is able to give guidance, let alone us who are only human beings, the Prophet Muhammad SAW, are not able to. Prophet Muhammad SAW and we are only given the obligation to call (preach).